Factors of Women’s Inclusion into the Scientific Sphere and their Participation in Study of Siberia in Second Half of the XIX - Early XX Centuries - E. V. Igumnov (Научный диалог, 2020)
The results of a study on the participation of women in the study of the Siberian region in the second half of the XIX - early XX centuries are presented in the article. It is noted that women constantly had to face various obstacles and difficulties on the scientific path, caused by gender stereotypes, while the position of women in Siberian society had certain characteristics. The factors of women's inclusion into the scientific sphere are revealed in detail: the development of the educational system, the emergence of the first higher educational institutions, the creation of scientific institutions, the formation of civic consciousness, joint scientific studies and the legitimization of scientific activity through spouses. The main directions of local history research are shown. On the example of the activities of M. I. Molleson, V. A. Balandina, A. D. Kornakova, M. V. Krasnozhenova and others, the contribution of women to the description of nature and climate, natural resources, ethnography of the peoples of Siberia, the establishment of museum business is examined. Separately, the author pays attention to female charity for the needs of science in the Siberian region. Significant funds for research purposes were donated by E. P. and Yu. P. Kuznetsovs, A. I. Gromova, E. I. Goldobina. The activities of some Siberians were highly appreciated by contemporaries and awarded by scientific institutions of Russia. When writing the article, the author used numerous reports and works of scientific and local history organizations, which made it possible to identify the names of many women who participated in their work.